2020
DOI: 10.1111/jfpp.14739
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, rheological, and sensorial properties of bread supplemented with pumpkin powder and basil seed gum

Abstract: This study aims at evaluating the impact of pumpkin powder (12%) and Basil seed gum (BSG) (0.00%, 0.50%, 1.00%, and 1.50%) on the physicochemical, rheology, textural properties, and sensorial parameters of sangak bread. First, the fresh pumpkin slices (5mm thickness) were dried (hot air, 65°C) and samples were powdered and used in sangak bread formulation. Pumpkin bread dough formulated with basil gum showed pseudoplastic and thixotropic behavior. The bread dough viscosity increased from 10.95 to 21.53 with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Breads have high nutritional value and are widely consumed worldwide; moreover, they feature different textures, shapes, toppings, and fillings. Bread is manufactured from whole wheat flour, baker's yeast, salt, and water [1]. In pan bread, also known as loaf bread or sliced bread, the dough is baked in a loaf pan, resulting in its characteristic form.…”
Section: Introductionmentioning
confidence: 99%
“…Breads have high nutritional value and are widely consumed worldwide; moreover, they feature different textures, shapes, toppings, and fillings. Bread is manufactured from whole wheat flour, baker's yeast, salt, and water [1]. In pan bread, also known as loaf bread or sliced bread, the dough is baked in a loaf pan, resulting in its characteristic form.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of bread increased, and during baking it decreased. Bread with pumpkin powder and 1.5 % basil seed gum had the best porosity and appearance, while bread with 1 % was the most satisfactory in terms of textural properties [9].…”
Section: Food Science and Technologymentioning
confidence: 97%
“…The increase in volume can be caused by the increase in the viscosity of the batter samples. In fact, a higher apparent viscosity helps to trap air in the batter and creates a higher volume and porosity in the samples, and in the low viscosity of the batter, air bubbles can easily rise to the surface of the batter and leave the environment [30]. Statistical comparison of the results related to the two protein groups indicated that WPC at 10% level, along with 0.15% or 0.3% of XG, played a greater role in increasing the specific volume of the cake samples.…”
Section: Storage and Lossmentioning
confidence: 99%